Translation and Validation of Marital Scales: Measurement of Intent, Attitudes and Aspects of Marital Relationships - Bashir, Rabia; Kazmi, Syeda Farhana; Naz, Summaira (Pakistan Languages and Humanities Review, 2024)
This study aimed to have culturally equivalent and linguistically precise measure of MAES in (Urdu) version. Women desire for autonomy, educational preferences, emphasis on careers are associated with delayed marriages in recent years. Excessive rise of marital problems within Pakistani culture arouses the dire need of an objective instrument to measure people attitude and aspects towards marriage. MAES comprising Intent to Marry Scale, General Attitudes toward Marriage Scale, and Aspects of Marriage Scale (Park & Rosen, 2013) was administered on adults using purposive sampling technique. First model (GAMS) included two factors, positive attitude and doubts towards marriage indicating adequate factor loadings, significant correlation, and appropriate fit. Second model (AMS) constituted three dimensions, aspect of trust, self-completion and compatibility for marriage depicting acceptable factor loadings, strong correlation, and satisfactory fit.